POETRY AND CARTOGRAPHY: काव्यचित्र एवं चित्रकाव्य - Joshi, Anita (International Journal of Research -GRANTHAALAYAH, 2019)
Art and poetry complement each other. The incorporation of poetry into fine arts and fine arts into poetry has given both poetry and art a plushness and fascination. The paper presented explains this interrelationship of poetry and painting, in which the similarity of painting and poetry, contribution to the creation of poetic images and expression in poetry painting have been embodied. कला एवं काव्य एक-दूसरे के पूरक हैं। ललित कलाओं में काव्य और काव्य में ललित कलाओं के समावेश ने काव्य एवं कला दोनों को ही सरसता एवं मोहकता प्रदान की है। प्रस्तुत शोधपत्र काव्य एवं चित्रकला के इसी अंतःसंबंध की व्याख्या करता है, जिसमें चित्रकला एवं काव्य की समानता, चित्रों का काव्य सृजन में योगदान एवं काव्यानुभूतियों की चित्रकला में अभिव्यक्ति को मूर्त रूप दिया गया है।